Circuit optimization technique of nonvolatile logic-in-memory based lookup table circuits using magnetic tunnel junction devices. (January 2019) - Suzuki, Daisuke; Oka, Takahiro; Hanyu, Takahiro
Abstract: A circuit optimization technique of nonvolatile logic-in-memory (NVLIM)-based lookup table (LUT) circuits in conjunction with magnetic-tunnel junction (MTJ) devices is proposed. Three important points should be considered for the circuit optimization technique of the NVLIM-based LUT circuit. One is optimizing DC and transient characteristics of the read current path, another is minimizing the effect of capacitance of both read-access transistors and write-access transistors, the other is how to design the selector circuit. As a typical example, the NVLIM-based LUT circuits is designed using 55 nm CMOS technology with two types of MTJ devices; the output delay, power and area of the circuit are evaluated. As a result, the output delay in the NVLIM-based 6-input LUT circuit is reduced by 47% compared to that of conventional SRAM-based implementation with 27% lower active power consumption as well as 67% of area reduction.